Efektifitas Dakwah Dialogis Melalui Radio Terhadap Pemahaman Agama Masyarakat Jember: The Effectiveness of Dialogical Da'wah through Radio on the Religious Understanding of the Jember Community - Thayib, Thayib (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2002)
The rapid development of science and technology has posed significant challenges for religious life, necessitating innovative, dialogical approaches to Islamic da’wah that can serve as a moral filter. This study addresses the gap in understanding how interactive radio programs function as effective media for religious communication. The research aimed to measure the effectiveness of dialogical da’wah through Prosalina FM in improving religious understanding among the people of Jember. A quantitative correlational approach was employed, involving 44 respondents selected through accidental sampling from listeners who actively participated in the Diaparis (Dialog Pakar Islam) program. Data were collected using questionnaires, interviews, and documentation, then analyzed using the Chi-square formula and Contingency Coefficient (KK). The results showed a Chi-square value of 9.57, which is higher than the table value of 3.84 at a 5% significance level, indicating a significant effect. The KK value of 0.42 falls within the range of 0.40–0.70, signifying a moderately meaningful level of effectiveness. The study concludes that dialogical da’wah via radio is significantly effective in enhancing religious understanding. It is recommended that such programs be maintained, expanded in broadcast frequency, and adapted to address increasingly complex religious needs. Perkembangan ilmu pengetahuan dan teknologi yang pesat telah menimbulkan tantangan signifikan bagi kehidupan beragama, sehingga diperlukan pendekatan dakwah Islam yang inovatif dan dialogis yang mampu menjadi filter moral. Penelitian ini menjawab kesenjangan pemahaman mengenai bagaimana program radio interaktif berfungsi sebagai media komunikasi keagamaan yang efektif. Tujuan penelitian ini adalah mengukur efektivitas dakwah dialogis melalui Prosalina FM terhadap peningkatan pemahaman agama masyarakat Jember. Pendekatan kuantitatif korelasional digunakan dengan melibatkan 44 responden yang dipilih secara accidental sampling dari pendengar aktif program Diaparis (Dialog Pakar Islam). Data dikumpulkan melalui kuesioner, wawancara, dan dokumentasi, kemudian dianalisis menggunakan rumus Chi-kuadrat dan Koefisien Kontingensi (KK). Hasil penelitian menunjukkan nilai Chi-kuadrat sebesar 9,57, lebih tinggi dari nilai tabel 3,84 pada taraf signifikansi 5%, yang berarti signifikan. Nilai KK sebesar 0,42 berada pada rentang 0,40–0,70, menandakan tingkat efektivitas yang cukup berarti. Penelitian ini menyimpulkan bahwa dakwah dialogis melalui radio efektif secara signifikan dalam meningkatkan pemahaman agama. Disarankan agar program semacam ini dipertahankan, diperluas frekuensi siarannya, dan disesuaikan dengan kebutuhan keagamaan masyarakat yang semakin kompleks.